Fatigue crack growth rate of two pearlitic rail steels. (April 2015) - Maya-Johnson, S.; Ramirez, A.J.; Toro, A.
Graphical abstract: Highlights: Two types of rail steels in two different orientations were studied. Complete crack growth curves of two rail steels were obtained. Correlations between the interlamellar spacing and the mechanical properties of the pearlitic steels were studied. The Paris–Erdogan Law coefficients ( m and C ) were estimated. The values of the fatigue crack growth threshold (Δ K th ) and the plane-strain fracture toughness ( K Ic ) were obtained. Abstract: A study of fatigue crack growth rate was conducted in two pearlitic rail steels, namely R260 and R370CrHT. Two crack plane orientations with respect to the rolling direction were tested and separate experiments were performed to cover a wide variation in fatigue crack growth, from the fatigue threshold (circa 10 −9 m/cycle) to rapid fracture conditions. The fracture surfaces were examined and some correlations between microstructural features such as interlamellar spacing and mechanical properties were made.